1972
DOI: 10.1901/jaba.1972.5-443
|View full text |Cite
|
Sign up to set email alerts
|

SELF‐REGULATION IN THE MODIFICATION OF DISRUPTIVE CLASSROOM BEHAVIOR1

Abstract: This study compared self-regulation and external regulation procedures in the treatment of children's disruptive dassroom behavior. After baseline data were collected, three of the four most disruptive children in each of 10 first-and second-grade dassrooms received reinforcement for achieving low rates of disruptive behavior. The fourth child served as a control subject throughout the experiment. Two of the three experimental subjects were then taught to self-observe their own disruptive behavior. In the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
71
1
1

Year Published

1974
1974
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(79 citation statements)
references
References 17 publications
6
71
1
1
Order By: Relevance
“…For instance, the manager may give himself an extra coffee break for having a clean desk the preceding day or stay after work for a half hour for each day that the paperwork is not taken care of. A number of studies in educational and clinical psychology have clearly demonstrated the effectiveness of self-recording, self-reward, and self-punishment [Bucher & Fabricatore, 1970;Broden, Hall, & Mitts, 1971;Johnson & White, 1971;Bolstad & Johnson, 1972;Flannery, 1972;Sobell & Sobell, 1973;Axelrod, Hall, Weiss, & Rohrer, 1974] and our own work has shown that it works in a managerial setting .…”
Section: Social Learning Theory In Perspectivementioning
confidence: 72%
“…For instance, the manager may give himself an extra coffee break for having a clean desk the preceding day or stay after work for a half hour for each day that the paperwork is not taken care of. A number of studies in educational and clinical psychology have clearly demonstrated the effectiveness of self-recording, self-reward, and self-punishment [Bucher & Fabricatore, 1970;Broden, Hall, & Mitts, 1971;Johnson & White, 1971;Bolstad & Johnson, 1972;Flannery, 1972;Sobell & Sobell, 1973;Axelrod, Hall, Weiss, & Rohrer, 1974] and our own work has shown that it works in a managerial setting .…”
Section: Social Learning Theory In Perspectivementioning
confidence: 72%
“…For example, peer-group control of inappropriate behavior has often been suspected and sometimes documented (Buehler, Patterson, and Furniss, 1966;Gelfand, Gelfand, and Dobson, 1967;Solomon and Wahler, 1973 Bolstad and Johnson (1972) presented data that showed that both experimental and control subjects in the same classroom were all affected (although not to the same extent) by experimental manipulation of the reinforcement contingency for the experimental subjects, whereas control subjects in a different classroom were not so affected. The authors presented data that may account for these differences.…”
Section: Sequential Modificationmentioning
confidence: 99%
“…Self-control training, diffusely defined, encompasses a variety of techniques which are designed to help students assume more and more of the direct management of their own academic achievement and classroom deportment. Self-control researchers have demonstrated: (a) Grade school children can effectively be taught to self-monitor, self-evaluate, and self-reinforce contingently for academic and classroom behaviors under externally imposed, experimenter contingencies (Ballard & Glynn, 1975;Bolstad & Johnson, 1972;Clement, Anderson, Arnold, Butman, Fantuzzo, & May, 1978;Glynn, Thomas, & Shee, 1973 (SUMMER 1984) equally effective (Bolstad & Johnson, 1972;Fredericksen & Fredericksen, 1975) or more effective (Edgar & Clement, 1980;Parks, Fine, & Hopkins, 1974) than externally administered and determined procedures. (c) Students can determine their own performance standards and contingencies, and when combined with reinforcement, these self-determined contingencies are either as effective (Felixbrod & O'Leary, 1973 or more effective (Brownell, Colletti, Ersner-Hershfield, Hershfield, & Wilson, 1977;Lovitt & Curtiss, 1969) than externally determined contingencies.…”
mentioning
confidence: 99%